PENGARUH BUDAYA ORGANISASI DAN KONSEP DIRI TERHADAP PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN JAGAKARSA, JAKARTA SELATAN - Nurhidayati, Rina (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2015)
Abstract: This research is made to determine (1) the influence between organizational culture to decision making head of state primary school, (2) the influence self concept to decision making head of state primary school, and (3) the influence organizational culture to self concept head of state primary school. The research methodology that has been used was survey with path analysis technique in testing hypothesis. In this study, 54 head of state primary school have been used as a sample by using simple random sampling techniques(simple random sampling). This research conducted in Jagakarsa, South-Jakarta area. Based on the description of hypothesis test, the researches findings can be outlined as followed: (1) there is a positive influence between organizational culture to decision making head of state primary school, (2) there is a positive influence self concept to decision making head of state primary school, and (3) there is a positive influence organizational culture to self concept head of state primary school. The implication of this study is attempt of improving the decision making head of state primary school that can be done through improveorganizational culture and self concept.Keywords: decision making, self concept, organizational culture.